Short-Term Psychological Outcomes in Severely Obese Adolescents After Bariatric Surgery - Järvholm, Kajsa; Olbers, Torsten; Marcus, Calude; Mårild, Staffan; Gronowitz, Eva; Friberg, Peter; Johnsson, Per; Flodmark, Carl-Erik (Obesity, 2012)
Bariatric surgery is suggested as a treatment option for severely obese adolescents. Because adolescence is characterized by intense psychosocial adjustment and development, it is important to study the effect of this procedure on adolescents' psychological health. This study examined baseline status and short-term changes in anxiety, depression, anger, disruptive behavior, and self-concept in 37 adolescents (mean age 16.6 ± 1.3). Participants completed the Beck Youth Inventories (BYI) at inclusion and (on average) 4 months after undergoing Roux-en-Y gastric bypass (RYGB). Internalizing (anxiety and depression) and externalizing (anger and disruptive behavior) symptoms were higher at baseline than gender-specific norms. One fifth had a very low self-concept. Four months after surgery, the adolescents showed significantly fewer symptoms of anxiety and depression and significantly improved self-concept from baseline. Anger and disruptive behavior showed no significant changes. An analysis of clinically meaningful changes was conducted, and besides the overall positive outcome, 16% (n = 6) of the adolescents had deteriorated on two or more inventories in BYI shortly after surgery. This impaired group did not show any specific features at inclusion. The results indicate the importance of psychological monitoring immediately after bariatric surgery and the need for additional psychosocial support to be available for vulnerable sub-groups of adolescents. Further studies with larger samples are necessary to identify characteristics predictive of short-term adverse psychological outcomes in adolescents after bariatric surgery.